The Environmental Impact of ‘Superfoods’: A Space for Debate and Joint Reflection - Ana Fernández-Ríos; Jara Laso; María Margallo; Rubén Aldaco (Biology and Life Sciences Forum, 2022)
This paper aims to provide an overview of the environmental impacts of superfoods. For this purpose, a bibliographic search was conducted to find articles developing the life cycle assessment of four of the most popular superfoods (quinoa, chia, spirulina, and kale), as well as to identify potential future environmental challenges. The main outcomes reveal that: (1) with the limited information that is currently available, it cannot justifiably be claimed that superfoods present environmental benefits compared to traditional products, and (2) the environmental impacts will increase in the medium-to-long term due to the change of current agricultural systems into intensive commercially oriented systems caused by demand growth.